2002
DOI: 10.1177/10791102009002007
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Beck Depression Inventory–Ii Subscales in Screening for Major Depressive Disorders in Adolescent Psychiatric Inpatients

Abstract: The Beck Depression Inventory-II (BDI-II) was administered to 45 male and 55 female psychiatric inpatients who were 12 to 17 years old, and the Mood Module from the Primary Care Evaluation of Mental Disorders (PRIME-MD) was used to determine whether these patients met criteria for a diagnosis of a DSM-IV major depressive disorder (MDD). Binormal receiver-operating-characteristic (ROC) analyses found that BDI-II total scores, Cognitive subscale scores, Noncognitive subscale scores, and embedded BDI FastScreen f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 17 publications
6
68
0
1
Order By: Relevance
“…The BDI-II showed a high level of internal consistency, in line with previous studies (e.g. Krefetz et al, 2002;Kumar et al, 2002;Osman et al, 2004). The mean BDI-II score was similar to those reported by other studies with adult offender samples in England (Palmer and Connelly, 2005;mean 15.13) and Ireland (Eidhin et al, 2002;mean 16.31).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The BDI-II showed a high level of internal consistency, in line with previous studies (e.g. Krefetz et al, 2002;Kumar et al, 2002;Osman et al, 2004). The mean BDI-II score was similar to those reported by other studies with adult offender samples in England (Palmer and Connelly, 2005;mean 15.13) and Ireland (Eidhin et al, 2002;mean 16.31).…”
Section: Discussionsupporting
confidence: 88%
“…Research showing that individuals with a diagnosis of depression score signifi cantly higher than those without depression on the BDI-II provides evidence for criterionrelated validity (Osman et al, 2004). Convergent and discriminant validity are evidenced by research reporting BDI-II scores to be more strongly correlated with other measures of depression than assessments of constructs such as anxiety among adults and adolescents (Krefetz et al, 2002;Kumar et al, 2002;Osman et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Steer et al (1998) and Krefetz et al (2002) reported similar alpha estimates (i.e., a 5 .92) in separate samples of adolescent psychiatric patients. Kumar et al (2002) reported an alpha estimate of .94 for the BDI-II with adolescent outpatients (N 5 100), and Osman et al (2004) also recently reported a similar alpha estimate of .93 with a large sample (N 5 408) of adolescent psychiatric inpatients. Note, however, that only Osman et al's investigation followed current psychometric guidelines of reporting other internal consistency estimates such as the average interitem correlations for the BDI-II scores (see Clark & Watson, 1995).…”
mentioning
confidence: 71%
“…The related conditional probabilities (e.g., sensitivity 5 74%, specificity 5 70%), and the area under the curve (AUC 5 .78) estimates indicated moderate accuracy in differentiating the responses of the groups. Kumar et al (2002) attempted to replicate the ROC procedure of Krefetz et al (2002) in a similar sample of adolescents with or without DSM-IV diagnosis of MDD. Using scores on the total BDI-II, the two BDI-II scale scores (Cognitive and Non-Cognitive), and a seven-item total BDI-II scale score (the Beck Depression Inventory FastScreen for Medical Patients; Beck, Steer, & Brown, 2000), the authors reported better discriminative evidence for the different ways of scoring the BDI-II.…”
mentioning
confidence: 99%